2013
DOI: 10.1002/oby.20664
|View full text |Cite
|
Sign up to set email alerts
|

Retrograde gastric electrical stimulation suppresses calorie intake in obese subjects

Abstract: Objective: The effect of acute retrograde gastric electrical stimulation (RGES) on food intake, gastric accommodation, and gastric emptying in obese patients was investigated. Methods: Simple obesity patients underwent RGES or sham stimulation. The maximum food intake volume was determined and the total calorie of consumed food was calculated. Conclusions: Acute RGES reduces calorie intake by decreasing gastric accommodation in obese subjects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Two studies, one from TANTALUS ® [39] and the other from gastric pacing [40] , found lower ghrelin levels after device activation. However, three studies, two from IGS [41,42] and another TANTALUS ® [43] study, found no statistically significant changes in ghrelin levels. Another interesting find was that 4 studies, including 2 RGES [41,44] studies and 2 gastric pacing [42,45] studies, demonstrated delayed gastric emptying whereas one TANTALUS ® study demonstrated the opposite effect.…”
Section: Co-morbiditiesmentioning
confidence: 95%
“…Two studies, one from TANTALUS ® [39] and the other from gastric pacing [40] , found lower ghrelin levels after device activation. However, three studies, two from IGS [41,42] and another TANTALUS ® [43] study, found no statistically significant changes in ghrelin levels. Another interesting find was that 4 studies, including 2 RGES [41,44] studies and 2 gastric pacing [42,45] studies, demonstrated delayed gastric emptying whereas one TANTALUS ® study demonstrated the opposite effect.…”
Section: Co-morbiditiesmentioning
confidence: 95%
“…65 The mechanisms of action include changes in gastric emptying or gastric accommodation and induction of satiety. 66,67 …”
Section: Novel Devices Proposed In Obesity Treatment and Their Potentmentioning
confidence: 99%
“…Acute retrograde gastric electrical stimulation is a process in which electrodes are endoscopically placed into the stomach to simulate satiety [36]. One study (n ¼ 16) found a significantly reduced caloric intake among patients with electrodes placed in their stomach, but the study did not examine weight loss as an outcome [37].…”
Section: Electrical Stimulation (Fda Status: Not Approved)mentioning
confidence: 99%